Nurturing Creativity in Indian Design Education: Insights and a Conceptual Mind Map - G. Chiranjeevi Reddy (International Journal of Arts Architecture & Design)
This study explores the perspectives of design educators in India on creativity as a critical skill in higher education, particularly in the context of the National Education Policy (NEP) 2020. Analyzing data from 131 educators who participated in a Faculty Development Program (FDP) focused on creativity, the research assessed the current state of creative exploration, interdisciplinary collaboration, and inclusivity in educational institutions. It identified significant gaps and proposed actionable strategies for improvement. A comprehensive mind map was also developed, integrating cognitive strategies, techniques, and traits to enhance creativity among educators and students. While 63% of educators regard creativity as essential, 30% believe their institutions lack sufficient creative thinking tools. While strong support exists for interdisciplinary collaboration (80.2%) and inclusivity (93.1%), 11% of educators report inadequate opportunities for creative exploration. The study emphasizes the need for enhanced training programs to improve educators’ proficiency with creative tools, the integration of design thinking and problem-solving methodologies into curricula, and the promotion of interdisciplinary projects to foster collaborative learning environments.